Genetic and transcriptional profiles of ammonia oxidizing communities in Bohai sediments: abundance, activity, and environmental correlations - Jiang, Yining; Lou, Xue; Wang, Mingyang; Zheng, Minggang; Wang, Zhiyao; Chen, Hui (Frontiers in Microbiology, 2025)
Ammonia oxidation, a crucial part in nitrogen cycle, is thought to be jointly driven by ammonia-oxidizing archaea (AOA), ammonia-oxidizing bacteria (AOB), and complete ammonia oxidation (comammox) in the ocean. However, the spatial distribution of these three ammonia-oxidizing microorganisms in the marine sediments, especially at the transcriptional level, remains underexplored. This study utilizes quantitative PCR and activity experiments to quantify the amoA gene of three ammonia oxidizers at both DNA and RNA levels, measure their potential nitrification rate, and assess their relative contribution to ammonia oxidation in the marine sediments in Bohai region in China. Further, we analyzed their correlations with key environmental factors. In the marine sediments of Bohai, the transcript abundance of AOA, AOB, and comammox amoA genes ranged from 7.31 × 102 to 9.82 × 104, 5.77 × 103 to 3.98 × 104 and 1.07 × 104 to 5.44 × 104 copies g−1 dry sediment, respectively. The results revealed that TN and TOC had significant effects on total amoA gene abundance and transcript abundance for all ammonia oxidizers. Besides, the relative contribution of AOB to ammonia oxidation was greater than that of AOA and comammox based on activity measurement, likely due to nitrate nitrogen and total nitrogen. Our study demonstrated that RNA-based amoA abundance and activity measurements can accurately reflect the spatial variations of ammonia oxidizers in Bohai sediments.